1997
DOI: 10.1103/physreve.56.472
|View full text |Cite
|
Sign up to set email alerts
|

Viscous effects in droplet-ejecting capillary waves

Abstract: Surface waves produced by parametric excitation experience a transition between simply connected waves and droplet-ejecting waves when the applied forcing exceeds a threshold level. Our measurements on a number of different fluids indicate that low-viscosity fluids have threshold accelerations which depend on only surface tension and forcing frequency while high viscosity fluids have thresholds which depend on only viscosity and forcing frequency. Models for the transition based on the condition that the wavel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
64
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 23 publications
12
64
1
Order By: Relevance
“…A subsequent work by Vukasinovic et al (2007b) focused specifically on the mechanism of breakup to form single ejected drops and large numbers of drops, which appear under different excitation conditions, and the lengths of jets that form from the capillary wave. Their results are similar to Goodridge et al (1997) for the transition to atomization, although they also found, for cases where the drop ejection does not directly depend upon the viscosity (i.e., the capillary number Ca ( 1), that the threshold acceleration depends only on a nondimensional drop size that is essentially the same as Eq. (74).…”
Section: =3supporting
confidence: 73%
See 1 more Smart Citation
“…A subsequent work by Vukasinovic et al (2007b) focused specifically on the mechanism of breakup to form single ejected drops and large numbers of drops, which appear under different excitation conditions, and the lengths of jets that form from the capillary wave. Their results are similar to Goodridge et al (1997) for the transition to atomization, although they also found, for cases where the drop ejection does not directly depend upon the viscosity (i.e., the capillary number Ca ( 1), that the threshold acceleration depends only on a nondimensional drop size that is essentially the same as Eq. (74).…”
Section: =3supporting
confidence: 73%
“…Although the mechanism of atomization was still unclear even 5 to 10 years ago, progress was being made: Goodridge et al (1997) identified a threshold acceleration that, once exceeded, gives rise to ejection of drops from the crests of the capillary wave; the threshold acceleration a is given by a / f 4=3…”
Section: Atomizationmentioning
confidence: 99%
“…Unlike previous critical power studies, 23 we cannot identify by eye the time at which critical power is reached; our droplets are too small to be seen individually by eye. We therefore rely on light scattering to detect the initial presence of droplets in our system.…”
Section: -mentioning
confidence: 64%
“…These constants have been measured experimentally by Goodridge et al and are found to be b 1 = 0.261 and b 2 = 1.306. 23 Because the physics which determines the critical acceleration-the minimum acceleration at which droplets are ejected from a driven surface-is different from that which determines the droplet's size once it is ejected, these two phenomena cross between the inviscid and viscous regime at different dimensionless frequencies. The crossover frequency for the diameter regimes is almost four orders of magnitude greater than that for the acceleration regimes.…”
Section: B Input Power Requirementmentioning
confidence: 99%
See 1 more Smart Citation